Video Recorder as an Object of Forensic Expert Analysis - S. A. Krutov (Теория и практика судебной экспертизы, 2021)
The article addresses the issues related to stationary video recorders: their types, purpose, principles of functioning, design characteristics, key components installed in these devices. The author analyses the procedure for using the video recordings from the surveillance cameras in court proceedings. He also justifies the need for comprehensive examinations when investigating stationary video recorders and points out the cases when the appointment of an examination is necessary and when a specialist inspection is enough. The paper presents a research sequence for a stationary video recorder as a computer forensics’ object. Possible questions to the expert, methods, and approaches are listed; difficulties arising during the examination are considered. The author analyzes a case study of a stationary video recorder examination from the expert practice of the laboratory of computer forensics of the Russian Federal Centre of Forensic Science of the Russian Ministry of Justice.